Complete denture parameters reflecting the satisfaction of dentists and patients - Ahmed, Abdul Razzaq; Chaturvedi, Saurabh; Das, Gotam; Khan, Muhammad Farhan; Suleman, Ghazala; Sibghatullah, Muhammad (Vojnosanitetski pregled, 2021)
Background/Aim. Patients’ expectations with regard to their complete dentures are usually high. It is quite challenging to meet the patient’s criteria for denture satisfaction. Moreover, it also becomes a challenging task when the patient’s expectation exceeds the patient’s satisfaction regardless of the denture quality. The aim of this study was to determine the correlation in the denture satisfaction levels between the dentist and complete denture wearers. Methods. The study included 134 completely edentulous participants, between 48 and 65 years of age. The data were recorded through a validated questionnaire having a Cronbach α validity of 85%. Sociodemographic data, patients’ priorities, dentists’ and patients’ satisfaction with the dentures were recorded and rated on a Likert scale (1 to 5). Spearman’s correlation was applied to measure the similarity between the dentist’s and patient’s satisfaction score. Results. The mean dentists’ and patients’ overall satisfaction scores were calculated as 3.58 ± 0.74 and 3.538 ± 0.521, respectively. Participants ≥ 60 years of age and females showed a higher correlation than younger patients and men, while the employed participants showed a stronger correlation between dentist’s and patient’s satisfaction, compared to the opposite. In the educated participants a positive, moderate correlation between dentist’s and patient’s satisfaction was shown. The correlation between dentist’s satisfaction with occlusion and patient’s satisfaction with comfort was moderately strong (p < 0.05); weakly positive correlation (p < 0.05) was found between dentist’s satisfaction with the quality of denture and extension and patient’s satisfaction with aesthetics, mastication, phonetics, and comfort. Conclusion. A positive correlation between the dentists’ and patients’ satisfaction regarding denture quality was shown in older-age patients, females, as well as employed and educated patients. Improving dentist-patient communication is the most useful strategy to improve patients’ satisfaction with their dentures.